2021
DOI: 10.1007/s10611-021-09984-9
|View full text |Cite
|
Sign up to set email alerts
|

The welfare of wildlife: an interdisciplinary analysis of harm in the legal and illegal wildlife trades and possible ways forward

Abstract: Wildlife trade—both legal and illegal—is an activity that is currently the focus of global attention. Concerns over the loss of biodiversity, partly stemming from overexploitation, and the corona virus pandemic, likely originating from wildlife trade, are urgent matters. These concerns though centre on people. Only sometimes does the discussion focus on the wildlife traded and their welfare. In this article, we make the case as to why welfare is an important component of any discussion or policy about wildlife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…In addition, as shown here, first-hand observations allow for the assessment of how well vendors adhere to welfare standards. This is increasingly recognised as an important component to assess sustainability of harvest and trade [ 64 , 69 , 70 , 71 ]. Baker et al [ 70 ] concluded that with regards to welfare and wildlife trade, a reasonable aspiration was to eradicate (or limit) that part of the trade that on welfare grounds is deemed irretrievably unacceptable and to improve animal welfare for the remaining parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as shown here, first-hand observations allow for the assessment of how well vendors adhere to welfare standards. This is increasingly recognised as an important component to assess sustainability of harvest and trade [ 64 , 69 , 70 , 71 ]. Baker et al [ 70 ] concluded that with regards to welfare and wildlife trade, a reasonable aspiration was to eradicate (or limit) that part of the trade that on welfare grounds is deemed irretrievably unacceptable and to improve animal welfare for the remaining parts.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al [ 70 ] concluded that with regards to welfare and wildlife trade, a reasonable aspiration was to eradicate (or limit) that part of the trade that on welfare grounds is deemed irretrievably unacceptable and to improve animal welfare for the remaining parts. Welfare, furthermore, can also be a tool for law enforcement, as attention to the welfare needs of trafficked wildlife can expose the modus operandi and become a tool for law enforcement [ 71 ]. Specifically, the relative high welfare needs of wild-caught birds (relative to for instance plants, reptiles, and certain mammals) necessitate a fast movement through the trade chain and this requires both an organised infrastructure and a good degree of planning.…”
Section: Discussionmentioning
confidence: 99%
“…Harms that are not criminalized can be as harmful as acts that are criminalized, and because what is criminalized varies in different times and within different social communities, green criminology scholars study harms as much as crimes (e.g., Brisman & South, 2014 ; Lynch & Stretesky, 2016 ; Sollund, 2015 ; White, 2013 ). The concept of harm is particularly relevant in the context of wildlife trade because everything an animal is exposed to as part of this trade is harmful ( Sollund, 2011 ; Wyatt et al, 2021 ), yet most of these harms take place within the limits of the law. For example, every year thousands of parrots are legally abducted and sent from Latin America to countries such as Russia and Singapore to be “pets” in private households ( Sinovas et al, 2017 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…CITES does not protect animals from trade before their species is threatened with extinction. CITES also has little concern for the welfare of individual animals who are victims of trade ( Goyes & Sollund, 2016 ; Mulà Arribas, 2015 ; Sollund, 2019 ; Wyatt et al, 2021 ), and partial protection is awarded only to those species that are listed on the CITES appendices. Currently 5,950 species of animals and 32,800 species of plants have some protection in CITES, but far more species never reach any appendix.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the EFM, the Green Criminology has the task of analyzing all the criminal processes connected to the natural environment [ 37 , 38 , 39 ]. The green criminology addresses forms of crime that harm the environment, but that are often ignored in the mainstream criminological research [ 40 ].…”
Section: Environmental (Green) Criminologymentioning
confidence: 99%